Functional Features of Forensic Corruption Case in Indonesia - Sinar, T S (KnE Social Sciences, 2018)
This study examines the multimodal use of language affecting the social interaction in the Indonesian Court for Corruption Crimes as the research data source. The objective is to analyze the metafunction multimodal functional features of law enforcement and witnesses in the proceedings of forensic corruption case in Indonesia. Multimodal theory as a new technology that has been invented by linguists was used in this research to analyse forensic language. The findings showed that the multimodal systems were valuable in analysing the forensic functional features in the court room and the functional features of representational, interactive and compositional meanings were present in the court room involving gestures, postures, gazes, nonverbal communication, eye contacts, etc. Keywords: functional features, multimodal, forensic corruption case.